Statistical mechanical modeling of the transition Stage II → Stage I of Li-ion storage in graphite. A priori vs induced heterogeneity - Otero, Manuel (2017)
An improved model to analyze the partial molar entropy step between stage II and stage I for lithium intercalation in graphite, based in statistical mechanics, is presented. At difference with our previous formulation, which assumed a priori heterogeneities, the present model considers the more realistic case of induced heterogeneities. The present work shows that, similarly to considerations made in the literature with intercalation cathode materials, most of the partial molar entropy changes for Li insertion into graphite may be explained on a configurational basis. The interaction between ions intercalated in a same layer of graphite can be inferred to be strongly attractive, as was assumed in the literature for the simulation of voltammetric profiles.